2012
DOI: 10.1039/c2nr30444a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis and characterization of subnanometre-size benzotriazolate protected copper clusters

Abstract: A simple one-pot method for the preparation of subnanometre-size benzotriazolate (BTA) protected copper clusters, Cu(n)BTA(m), is reported. The clusters were analyzed by optical and infrared spectroscopy, mass spectrometry and transmission electron microscopy together with computational methods. We suggest a structural motif where the copper core of the Cu(n)BTA(m) clusters is protected by BTA-Cu(i)-BTA units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…22 For this reason, copper clusters are currently a hot subject of research, 23,24 and several quantum chemical studies concerning the structure and electronic nanoparticles are placed in a unit cell that is periodically repeated in the three dimensions of space, and that employ plane wave basis sets within a reciprocal space representation that lead to a reduction in the computational scaling to N 2 or even N. [44][45][46] A key advantage of this approach is that small, intermediate size and large transition metal clusters or nanoparticles, as well as the upper size limit represented by extended surfaces, can be studied using a single methodology. [47][48][49] However, since this method was initially conceived for solids, its accuracy when describing molecular systems might be less than that of DFT methods using atom-centered functions as basis sets.…”
Section: Introductionmentioning
confidence: 99%
“…22 For this reason, copper clusters are currently a hot subject of research, 23,24 and several quantum chemical studies concerning the structure and electronic nanoparticles are placed in a unit cell that is periodically repeated in the three dimensions of space, and that employ plane wave basis sets within a reciprocal space representation that lead to a reduction in the computational scaling to N 2 or even N. [44][45][46] A key advantage of this approach is that small, intermediate size and large transition metal clusters or nanoparticles, as well as the upper size limit represented by extended surfaces, can be studied using a single methodology. [47][48][49] However, since this method was initially conceived for solids, its accuracy when describing molecular systems might be less than that of DFT methods using atom-centered functions as basis sets.…”
Section: Introductionmentioning
confidence: 99%
“…In the negative mode only the smaller species, such as, CuL 2 and BTA anions were present and clusters were no longer found. 32 One more Cu cluster protected by 2-phenylethanethiol (PET) was reported in 2013. 45 It was prepared by following the solid -state route.…”
Section: Cu Clustersmentioning
confidence: 99%
“…rRSC Publishing. Reproduced with permission 32. (C) a) MALDI MS of the PET protected Cu clusters measured in linear negative ion mode, measured using DCTB matrix.…”
mentioning
confidence: 99%
“…Nowadays, there is a growing demand on nonprecious‐metal catalysts due to a limited amount of precious metals, and the catalytic activity of copper nanoclusters has emerged as one of the promising candidates in various areas of sensing, biolabeling, and catalysis . This is apparent reason that copper clusters are currently the hot topics in research.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have shown that bimetallic nanoalloys are better catalyst than pure metals and they are in demand in various commercial electrocatalytic and catalytic processes . Therefore, researchers envisioned that copper clusters doped with different transition‐metal atoms will be a new kind of molecular architecture to provide the desired structural, electronic, magnetic, optical and catalytic properties for potential applications in nanotechnology, materials science, microelectronics, biology, medicine, and solid‐state chemistry …”
Section: Introductionmentioning
confidence: 99%